Early detection of pulmonary arterial hypertension through [18F] positron emission tomography imaging with a vascular endothelial receptor small molecule - Zhen Yang; Feng Li; Rajarajan A. Thandavarayan; Kartiga Natarajan; Diego R. Martin; Zheng Li; Ashrith Guha (Pulmonary Circulation, 2024)
Abstract The objective of this study is to provide a positron emission tomography (PET) imaging modality targeting vascular endothelial growth factor receptors (VEGFR) for the early noninvasive detection and assessment of pulmonary arterial hypertension (PAH) severity. To validate the effectiveness of the [18F]VEGFR PET tracer, we utilized a monocrotaline (MCT)‐induced PAH rat model. Molecular optical imaging, using a Cy5.5‐conjugated VEGFR targeting agent, was employed to demonstrate the uptake of the agent at pulmonary arterioles, correlating with the onset and progression of PAH. Histological examinations of the MCT‐PAH rat lung revealed a significant correlation between VEGFR2 expression and the pathogenesis of PAH. Molecular optical imaging demonstrated heightened uptake of the Cy5.5‐conjugated VEGFR targeting agent at pulmonary arterioles, corresponding with the onset and progression of PAH. [18F]VEGFR PET showed increased lung uptake detectable in early‐stage PAH before increase in pulmonary artery pressures, and this uptake correlated with increased PAH severity. Moreover, when compared to [18F]FDG PET, [18F]VEGFR PET exhibited markedly lower background cardiac signal, enhancing imaging sensitivity for lung abnormalities. Our study provides a compelling evidence for the potential utility of the innovative [18F]VEGFR PET tracer, in non‐invasively detecting early signs of PAH, and monitoring its progression. The observed correlations between VEGFR2 expression, molecular optical imaging results, and [18F]VEGFR PET findings support the use of this tracer for early detection, and assessment of PAH severity. The lower background cardiac signal observed with [18F]VEGFR PET further enhances its imaging sensitivity, emphasizing its potential clinical significance.